After apartheid: The effects of ANC power - Jonas Poulsen (Uppsala University, Department of Economics, 2013)
The African National Congress (ANC) can look back on eighty years of struggle which resulted in the liberation of black Africans, the creation of a democratic constitution and free elections. However, the last twenty years of ANC rule has been criticized for the failure to bring higher living standards for the formerly oppressed. With the party's dominance and the challanges facing South Africa in mind, I estimate the effect of ANC power in municipalities on economic, social and budgetary outcomes. To estimate the causal effect of the party, this paper uses an instrumental variable approach developed by Freier & Odendahl (2012) and a regression discontinuity design. Taken together, the results point to an adverse effect of the party: less is spent on repairs and water provision which in turn may explain why ANC power seems to lower the share of individuals who have access to piped water and electricity. Further, more resources are used on municipal employees and the councillors themselves, while I find suggestive evidence of an increase in the poverty rate due to the party. Lastly, although being their major political support, we cannot conclude that the ANC affects black African's living standards. From the IV analysis, I find indications that oppositional parties many times have a more positive impact on outcomes as they gain power at the expence of the ANC.
urn:nbn:se:uu:diva-207770
Keywords: O12; H11; N47; 330; ANC; party effects; instrumental variable; regression discontinuity; South Africa